Penambahan tepung mocaf dan bekatul pada kue Bangkit sebagai penambah serat makanan selingan remaja putri - Yulistia Avtina; Yuli Hartati; Sartono Sartono; Imelda Telisa; Podojoyo Podojoyo; Nurul Salasa Nilawati (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Fiber consumption among adolescents in Indonesia is still low. Efforts can be made to meet fiber consumption by innovating food products that teenagers like. One is adding mocaf flour and rice bran to Bangkit cake, which teenagers like.Objectives: The study aimed to produce the best Bangkit cake formula that is high in fiber and to calculate the contribution of nutrients from Bangkit cake to the nutritional and fiber adequacy of adolescents.Methods: Experimental study using a completely randomized design (CRD) with three treatments and one control. The subjects were 56 untrained panelists in the adolescent age group. Bangkit cake making was carried out in the Food Technology laboratory, and organoleptic tests were carried out in the sensory laboratory of the Palembang Polytechnic Nutrition Department. Nutrient analysis was conducted at Saraswanti Indo Genetech laboratory in Bogor. The research was conducted from July - September 2022. Organoleptic test data were processed by tabulating tested with the Kruskal Wallis test followed by the Mann-Whitney U test with a 95% confidence level.Results: Formula F3 is the best formula with the addition of 45% mocaf flour and 25% rice bran. With 473,07 Kcal/100 g energy, 6,15% protein, 19,71% fat, 67,77% carbohydrate, 2,12% ash, 4,25% water and 15,07% fiber. Each serving of Bangkit cake of as much as 50 grams (7 pieces) contributes 10% energy, 4,86% protein, 13,7% fat, 9,96% carbohydrate, and 23,83% fiber from the Recommended Dietary Allowances (RDA). There was a significant difference between the acceptability of Bangkit cake substituted with mocaf flour and rice bran on taste, texture, aftertaste, and overall (p≤0,05), and there was no difference between the acceptability of Bangkit cake modification on aroma and color (p>0,05).Conclusion: Bangkit cake contributes quite well in fulfilling nutrients, especially fiber. The acceptability of Bangkit cake substituting mocaf flour and rice bran is highly preferred in the taste, texture, aftertaste, and overall. However, the aroma and color are not so preferred.